Mechanical engineering for GATE - Slariya, Vikas (McGraw Hill Education (I) Pvt. Ltd, 2013)
Mechanical engineering for GATE / Slariya, Vikas. -- New Delhi: McGraw Hill Education (I) Pvt. Ltd., 2013 153.94621 Sl631e3 3rd ed No. of Copies : 1